1997
DOI: 10.1073/pnas.94.25.13582
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the oxidation potential and electron spin density of the primary electron donor in reaction centers from Rhodobacter sphaeroides

Abstract: The primary electron donor in bacterial reaction centers is a dimer of bacteriochlorophyll a molecules, labeled L or M based on their proximity to the symmetryrelated protein subunits. The electronic structure of the bacteriochlorophyll dimer was probed by introducing small systematic variations in the bacteriochlorophyll-protein interactions by a series of site-directed mutations that replaced residue Leu M160 with histidine, tyrosine, glutamic acid, glutamine, aspartic acid, asparagine, lysine, and serine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(132 citation statements)
references
References 32 publications
8
124
0
Order By: Relevance
“…Clearly, a regular hydrogen bond is not sufficient to provoke a shift of the spin density to the ring III. This is in line with the work on the bacterial RC (48), where it was found that hydrogen bonding and similarly weak interactions affect the redox potential only moderately by Ϸ50 mV, an order of magnitude less than the actual value reported for PS2. In this way our calculations imply that, if a protein-cofactor interaction at the ring V keto carbonyl oxygen is responsible for the increased redox potential, it should be very strong.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Clearly, a regular hydrogen bond is not sufficient to provoke a shift of the spin density to the ring III. This is in line with the work on the bacterial RC (48), where it was found that hydrogen bonding and similarly weak interactions affect the redox potential only moderately by Ϸ50 mV, an order of magnitude less than the actual value reported for PS2. In this way our calculations imply that, if a protein-cofactor interaction at the ring V keto carbonyl oxygen is responsible for the increased redox potential, it should be very strong.…”
Section: Resultssupporting
confidence: 72%
“…It has been shown that protein-cofactor interactions at the keto group of the BChl in the bacterial RC can increase the redox potential of the radical cations by stabilizing the orbital containing the unpaired electron (48). According to the photo-CIDNP, such a type of interaction may also be a predominant factor in generating the unusually high redox potential of 1.2 V of P 680 .…”
Section: Resultsmentioning
confidence: 99%
“…For deriving the polarizability of the LUMO(+) of P, we used the simple Hückel approach as described by Artz et al 40 The LUMOs of the two monomers were considered to be two one-electron states having nondiagonal coupling matrix elements, . 22 for Rps.…”
Section: Methodsmentioning
confidence: 99%
“…The spin density distribution of the BChla monomers of SP corresponds approximately to the charge distribution. Mutational studies on residues in the neighborhood of SP showed that its spin density dependents on the H-bond pattern of the BChla monomers [11,12]. Electrostatic computations suggested that small conformational changes of substituents at BChla can shift the midpoint redox potential for SP (E m (SP)), which should also affect the charge distribution pattern of the SP [13,14].…”
Section: Atomic Charges Of Spmentioning
confidence: 99%